World religions - Bowker, John Westerdale (New York : DK, 1997)
Looks at the beliefs and practices of many different religions, examining the sacred texts, imagery, key beliefs, and religious artifacts of Christianity, Judaism, Hinduism, Buddhism, Jainism, Sikhism, and Islam, and including discussion of ancient religions as well as Native, Chinese, and Japanese faiths.
Includes bibliographical references (p. 195) and index.
School Library Journal.
Wilson's Public Library.
Wilson's Senior High School.
Adult
Keywords: Religion -- Handbooks, manuals, etc; Religions -- Handbooks, manuals, etc; Religion -- Handbooks, manuals, etc; Religions -- Handbooks, manuals, etc